Analysis of Digital Literacy Interest Among Rural Communities in the Development of E-Government Systems - Raihan Chairunissa Kurniawan; Yanto Heryanto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The Electronic-Based Government System (SPBE) has been developed through various initiatives, significantly impacting the level of digital literacy among rural communities in Cirebon Regency. This study examines the results of an evaluation of the effectiveness of e-government policies using William N. Dunn’s policy evaluation framework. Data were collected using qualitative methods and an interview approach, with the Cirebon Regency Communication and Information Agency (Diskominfo) serving as the primary informant and two village officials in Palimanan Subdistrict as supporting informants. Field findings reveal that while digitization has successfully created bureaucratic efficiency and service transparency, aspects of access adequacy and equity remain hindered by infrastructure gaps and the digital generation divide. The research findings indicate that theoretical educational strategies have proven ineffective for rural communities; therefore, a practical, context-based mentoring approach is required through strategic collaboration between village governments, the Cirebon Regency Communication and Information Technology Agency (Diskominfo), and rural communities in Cirebon Regency. Thus, the success of digital transformation at the local level does not rely solely on technological sophistication but is heavily dependent on integrating system innovations with simpler literacy programs to ensure the digital self-reliance of communities even in the most remote villages, thereby realizing responsive and equitable governance.